Outcome of Laparoscopic Transperitoneal Ureterolithotomy for Proximal Ureteric Stones - Our Two Years Experiences (Medicine Today, 2018)
To evaluate the results of laparoscopic transperitoneal uteterolithotomy for management of large proximal ureteric stones. This study was performed on 24 patients having proximal ureteric stone greater than 1.5cm at the Department of Urology, Shahid Sheik Abu Naser Specialized Hospital, Khulna, Bangladesh from January 2016 to December 2017. Patients having stone size less than 1.5cm, previous abdominal surgery and sepsis were excluded from this study. Patients characteristics, stone characteristics, perioperative and follow-up data were studied. Twenty-four patients (mean age=52.9±12 years) with large upper ureteric stones (mean stone diameter=35±12) were included. Twenty-two patients had single stone and 2 patients had two stones. Mean operative time was 107±49.5 min with mean blood loss of 60.5±19.2 cc. Mean total pain score was 38.4±5.5 (100 point scale) and mean time resuming oral intake was 7.2±1 h. Mean duration of hospital stay was 2.6±1.4 days and mean time of stenting was 7.2±2 weeks. Throughout a mean duration of follow-up of 10.8±6.6 months 100% stone clearance rate was achieved with no recurrence. Laparoscopic transperitoneal ureterolithotomy is a safe and effective approach for selected patients with large proximal ureteric stones with reduced postoperative pain short hospital stays and cost effective and should be considered as a choice of treatment option for such stones.Medicine Today 2018 Vol.30(2): 71-73